PENGEMBANGAN MEDIA AJAR VIDEO DAN SOSIODRAMA PADA MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM KELAS IX MTS HIDAYATUL MUHAJIRIN PALANGKA RAYA - Firda Amalia Thoyibah; Nor Fadhila Herniyanti; Arman Nauli Nasution; Ristiani Arnila; Abdul Azis (CV. ADIBA AISHA AMIRA, 2024)
This research aims to develop video-based learning media and sociodrama in teaching Islamic Cultural History for grade IX students at MTs Hidayatul Muhajirin Palangka Raya. The background of this research highlights various obstacles in the learning process, such as lack of student participation and teaching methods that tend to be monotonous, which leads to low interest in learning. The methodology applied is Research and Development (R&D) with the ADDIE development model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. The results showed that the teaching media that had been developed were effective in increasing students' interest and understanding of the material on the development of pesantren and their role in Islamic propagation. The pilot test conducted showed that students showed higher enthusiasm and were more actively involved in the learning process. The conclusion of this research is that the use of video-based teaching media and sociodrama not only improves the quality of learning, but also deepens students' understanding of Islamic values, thus becoming a feasible recommendation to be applied more widely in the classroom education system.